Vaginal neutrophil infiltration is contingent on ovarian cycle phase and independent of pathogen infection - Latorre, M. C.; Gómez‐Oro, C.; Olivera‐Valle, I.; Blazquez‐Lopez, E.; Gallego‐Valle, J.; Ibañez‐Escribano, A.; Casesnoves, P.; González‐Cucharero, C.; Muñoz‐Fernandez, M. A.; Sanz, L.; Vaquero, J.; Martín‐Rabadań, P.; et al. (Frontiers in Immunology, 2022)
The mucosa of the female reproductive tract must reconcile the presence of commensal microbiota and the transit of exogenous spermatozoa with the elimination of sexually transmitted pathogens. In the vagina, neutrophils are the principal cellular arm of innate immunity and constitute the first line of protection in response to infections or injury. Neutrophils are absent from the vaginal lumen during the ovulatory phase, probably to allow sperm to fertilize; however, the mechanisms that regulate neutrophil influx to the vagina in response to aggressions remain controversial. We have used mouse inseminations and infections of Neisseria gonorrhoeae, Candida albicans, Trichomonas vaginalis, and HSV-2 models. We demonstrate that neutrophil infiltration of the vaginal mucosa is distinctively contingent on the ovarian cycle phase and independent of the sperm and pathogen challenge, probably to prevent sperm from being attacked by neutrophils. Neutrophils extravasation is a multi-step cascade of events, which includes their adhesion through selectins (E, P and L) and integrins of the endothelial cells. We have discovered that cervical endothelial cells expressed selectin-E (SELE, CD62E) to favor neutrophils recruitment and estradiol down-regulated SELE expression during ovulation, which impaired neutrophil transendothelial migration and orchestrated sperm tolerance. Progesterone up-regulated SELE to restore surveillance after ovulation.